KONSEP MENDIDIK ANAK MENJADI QURROTA A’YUN DALAM ISLAM (KAJIAN Q.S AL-FURQAN AYAT 74) - Attaqiya, Nida; Nasokha, Nasokha; Muntaqo, Rifki (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2019)
The aims of study are 1) knowing the concept of educating children in Islam, 2) knowing concept of children as an qurrota a’yun. 3) find out how to educate children to become qurrota a’yun. The type of research in this study is field research with qualitative methods, with in-depth analysis research techniques. Data collection that use in this study are, interpretation of Qur’an Surah Al-Furqaan, article that has related to the scripsi. Data analysis technique that using in this study was documentation study, and online data. The result of this study is showed that Qur’an surah Al-Furqaan: 74 explain the request of a servant to Allah SWT to be given wife and offspring in the household and a leader of household.